The Worthy Human Being as Prosuming Subject: ‘Projectified Selves’ in Emancipatory Project Studies - Berglund, Karin; Lindgren, Monica; Packendorff, Johann (Project management journal, 2020)
The projectified self is suggested in this article as a way to advance emancipatory project studies toward improved understandings of how individuals in contemporary neoliberal societies are urged to become self-controlling, self-improving, self-commercializing, life-compartmentalizing, and deadline driven. We propose (1) a developed theoretical foundation for studies of the projectified self, based on recent writings on enterprising selves, and (2) the notion of prosumption as a concept for how the worthiness of this projectified self is constructed in a simultaneous process of project-based production and consumption. This is discussed in relation to the on-going studies of social media entrepreneurs.